Protist communities of microbial mats from the extreme environments of five saline Andean lagoons at high altitudes in the Atacama Desert - Acosta, Eduardo; Nitsche, Frank; Dorador, Cristina; Arndt, Hartmut (Frontiers in Microbiology, 2024)
Heterotrophic protists colonizing microbial mats have received little attention over the last years despite their important role in the microbial foodwebs, as those found in the remote Andean lagoons. We sampled these mats from different isolated aquatic systems distributed across the Altiplano, where extreme radiation and wide temperature changes prevail, potentially structuring the microbial communities. Here, we present the results of the metabarcoding from DNA and cDNA of protists (V9) in microbial mats across high-altitude lagoons of different salinity (4.3-34 PSU), including insights into their vertical stratification. We assessed the DNA-based protists detected across all the study sites. However, for the cDNA-based analysis, amplification was achieved primarily in three study sites with lower salinity. Sequence variants classified as the amoeboid rhizarian Rhogostoma and as the ciliate Euplotes were found to be common members of the heterotrophic protist community in both the DNA and cDNA-based analyses of the studied lagoons. They were accompanied by diatoms and kinetoplastids.As detected through DNA, different ASVs classified as Rhogostoma and Neobodo are the shared species between the most saline lagoons. Furthermore, our analyses point to salinity of the water column as a main driver influencing the structure of the protist communities at the five studied microbial mats. The sequence of ASVs classified as Rhogostoma were highly similar to the sequence from R. olyaorum, a species recently isolated from the Atacama Desert. Our results provide a snapshot of the unculturable and active protist diversity thriving five athalossohaline lagoons from the Andean plateau.